KAJIAN TENTANG CLEARANCE DAN KECEPATAN KENDARAAN YANG MELAJU DI JALAN TOL (STUDI KASUS JALAN TOL LINGKAR LUAR JAKARTA) - Kusmaryono, Ismono (FSTPT Indonesia, 2015)
One of the problems cause road accidents is fault of clearance and speed. Research aimed at observing and analyzing the clearance and speed of vehicles on the highway. As a case study is a toll road in Jakarta Outer Ring Road KM 44 represent a flat road and KM 27 +700 represents downhill slope . The methodology used is the field observations and data analysis are presented with descriptive statistics and correlation analysis . The results showed that in therearenoappropriateclearancesafedistancebystoppingsight distance according to Highway Geometric Planning Standard for Toll Road and there is a speed exceeding the permitted speed limit as much as 51.6% on flat roads and on roads decreased by 18.8%. Another finding is the speed of the clearance from the exponential relationship y = 9.057e0,020x on a flat road location and establish a linear relationship on the way down with the equation y = 0.620x-1,941. Noappropriateclearancesafedistance and speed that exceeds the permitted speed limit causing safety aspects onatoll roadunfulfilled. Recommendations based on the research is the need for speed control and dissemination of the determination of the distance between the vehicle and driving speed in order to fulfill aspects of traffic safety.